An antioxidant and multivitamin supplement reduced improvements in VO2max - Skaug, A.; Sveen, O.; Raastad, T. (The Journal of Sports Medicine and Physical Fitness, 2014)
The aim of this study was to investigate the effect of an antioxidant supplement on training induced changes in VO2max in well-trained subjects. In a double-blinded placebo controlled design, a total of 40 amateur soccer players and 14 multi sports athletes were block-randomised into a placebo group or an antioxidant supplemented group (SUP). The SUP group consumed two commercially available antioxidant/vitamin supplements for 6 weeks according to manufacturer instructions (LifePak® Essentials Super A) and the placebo group took a similar amount of placebo tablets. Before and after the supplementation period, the athletes were tested for skin carotenoid score and VO2max. During the supplementation period all subjects continued their normal training in the preparation phase of the season. Six week supplementation with the antioxidant vitamin/mineral supplement increased skin carotenoid score by 27 ± 6% while no change was observed in the placebo group. VO2max increased by 5.6 ± 2.0% in the placebo group while no change was observed in the SUP group. The relative increase in VO2max was significantly higher in the placebo group than in the SUP group. In conclusion, the antioxidant vitamin/mineral supplement used in this study seemed to reduce training efficiency indicated by the lack of increase in VO2max in the SUP group.